IJCM_335A: Geriatric depression and associated factors: a community-based study in a rural area of Central Kerala - Chinky M; Bhaskar Anita (Wolters Kluwer Medknow Publications, 2024)
Background: Aging is a complex biological process associated with cellular and molecular damages. Rural India comprises 70 percent of the total geriatric population of the country. Kerala being a demographically advanced state have greater proportions of older population than the national average. Elderly constitutes a vulnerable group for depression, as they are especially prone to suffer adverse consequences of a depressive episode. Depression can cause great suffering and can lead to impaired functioning in daily life. Objective: : To estimate the prevalence of depression and determine the associated factors among elderly aged 60 years and above using Geriatric Depression Scale in Tholur Panchayath of Thrissur district, Kerala Methodology: A cross-sectional study was done among 200 older adults aged 60 years and above in October 2022 in Tholur village panchayat area of Thrissur District in Kerala. Using cluster sampling technique study participants were identified. After obtaining informed consent, a pretested questionnaire is administered to obtain sociodemographic characteristics and details of comorbid illness. The Geriatric Depression Scale, short-form questionnaire, was used as a screening tool for depression. Data was entered in MS Excel and statistically analyzed using the IBM SPSS software (trial version). Results: The mean age of the study population was 70.59 ± 7.89 years. 64.5% of the study population were females. 16.5% had mild depression, 10% had moderate depression and 11% had severe depression as per the geriatric depression scale (GDS) scoring. Conclusion: The prevalence of depression among the elderly was 37.8 %, and hence early diagnosis and prompt treatment are essential to reduce its burden in the community